Structural effect of Ni/ZrO2 catalyst on CO2 methanation with enhanced activity - Jia, Xinyu; Zhang, Xiaoshan; Rui, Ning; Hu, Xue; Liu, Chang-jun (Applied catalysis. B, Environmental, 2019)
[Display omitted] •The plasma decomposition leads to significantly improved Ni dispersion.•Ni(111) is the principally exposed facet on the plasma decomposed catalyst.•Oxygen vacancies created with enhanced Ni-ZrO2 interaction promotes CO2 adsorption.•A significantly improved activity is achieved over the plasma decomposed catalyst.•The plasma decomposed catalyst follows CO-hydrogenation route for CO2 methanation. A zirconia supported nickel catalyst for CO2 methanation has been prepared via a rapid and effective plasma decomposition of nickel precursor at atmospheric pressure and temperature around 150 °C, followed by hydrogen reduction at 500 °C. The obtained Ni/ZrO2 catalyst shows high Ni dispersion with principally exposed Ni(111) lattice plane. An enhanced cooperation between Ni and interfacial active sites is achieved as well, which leads to rapid dissociative adsorption of H2 and hydrogen spillover. Sufficient H atoms are thereby generated for CO2 hydrogenation and helpful to create oxygen vacancies on the ZrO2 surface. Higher basicity correlated to the oxygen vacancies further enhances CO2 adsorption and activation. Hence, a superior low temperature activity for CO2 methanation was achieved. For example, a CO2 conversion of 71.9% with a CH4 yield of 69.5% was achieved over the plasma decomposed catalyst at 300 °C with a feeding gas consisting of H2 (32 ml min−1), CO2 (8 ml min−1) and N2 (10 ml min−1) at a GHSV of 60,000 h-1. The corresponding TOF value towards CO2 conversion is 0.61 s-1. However, the CO2 conversion, CH4 yield and TOF value are only 32.9%, 30.3% and 0.39 s-1 at the same reaction conditions over the thermally prepared catalyst. The operando DRIFT analyses demonstrate that CO2 methanation over the plasma decomposed catalyst follows the CO-hydrogenation route. The exposed high-coordinate Ni(111) facets of the plasma decomposed catalyst facilitate the decomposition of CO2 and formates into adsorbed CO. The subsequent hydrogenation of adsorbed CO leads to the production of methane. However, the thermally decomposed catalyst with complex Ni crystal structure and more defects mainly takes the pathway of direct formate hydrogenation. The present study confirms the structure of Ni/ZrO2 has significant effect on the catalytic activity for CO2 methanation.